Managing Communities – Mining MNEs' Community Risk Management Practices - Jacob Taarup-Esbensen (Copenhagen Business School (CBS), 2018)
This PhD reflects the effort to close a gap in the multinational enterprise (MNE) risk management literature on the identification and mitigation of risk arising from local communities. Small villages and towns that are situated geographically close to the MNEs' place of operation have increasingly been identified as a source of risk (BSR, 2003; ICMM, 2015). The mining industry is one of the most exposed to risks from local communities, where there historically have been many conflicts between mine owners on one side and the people living close to the mine on the other (Godoy, 1985; Hoskin, 1912; Lynch, 2002; Morris, et al., 2012). And with access to new communication technologies, it is possible for even the remotest communities to communicate effectively to a wide global audience, enabling non-governmental organisations, politicians, investors and other civil society actors access to up-to-date information about mining MNE operations. This improved outreach has meant that mines have been closed due to conflicts with local communities and therefor a need had arisen for MNEs to implement management practices that can effectively mitigate these types of risks.
hdl:10398/9620
Keywords: 650